Preparation and evaluation of photoprotective kenaf seed oil nanocarriers-based cream of tocotrienol-rich fraction - Chu, Chee Chin; Tan, Chin Ping; Hasan, Zafarizal Aldrin Azizul; Nyam, Kar Lin (Elsevier, 2022)
Applications of nanotechnology and vegetable oil in topical formulation have emerged to provide benefits to develop effective and safe advanced biocosmetic prototypes. The study aimed to optimize the ratio of UV filters in kenaf (Hibiscus cannabinus L.) seed oil nanocarrier to form a sunscreen formulation. The nanocarriers were characterized based on particle size, polydispersity index, encapsulation efficiency, UV absorption, Raman microscopy, and high-resolution transmission electron microscopy analysis. The selected nanocarrier was added to a tocotrienol-rich fraction (TRF) cream and subjected to photoprotection and functional analysis to determine its skin beneficial properties based on cellular antioxidant capacity and relative protein expression on fibroblasts. The results revealed that nanocarriers with particle sizes ranging from 180 nm to 240 nm showed > 90% of encapsulation efficiency for UV filters. Sample F5 contained 1.25% of diethylamino hydroxybenzoyl hexyl benzoate (DHHB) and 0.75% of ethylhexyl triazone (EHT), having a spherical shape at particle size 204.80 nm with > 95% of UV filter encapsulation and high intensity in both UVA and UVB spectra. The cream produced from F5 and TRF (NLC-TRF cream) indicated no cytotoxicity and was able to provide sun protection factor (SPF) value of 53 and cellular antioxidant capacity of 45.13%. Besides, a significant protein upregulation (1.29-fold for fibroblast growth factor, 7.77-fold for vascular endothelial growth factor, 11.21-fold for transforming growth factor-β1, and 1.69-fold for tissue inhibitor matrix metalloproteinase-1) and downregulation for matrix metalloproteinase-1 and − 2 resulted after 24 hr of treatment. The application of nanocarriers in TRF cream can enhance the photoprotection, skin-protective properties in cellular antioxidant capacity, and protein expression which could be a promising delivery system in sunscreen formulations.